Reactive Arthritis in Children: Case Report, Narrative Review and Proposed Therapy - Alshaya, Milad; Almutairi, Nouf; Alrasheed, Abdulrahman; Albanaqi, Ihtifal; Laxer, Ronald M.; Alhammad, Abdullah (Current Pediatric Reviews, 2024)
Reactive arthritis is an acute inflammatory aseptic arthritis that is preceded by an infectious process in genetically predisposed individuals. It has been associated with gastrointestinal or genitourinary infection. Reactive arthritis is rare in children. In this review, we present two index cases that need biologic treatment followed by a thorough review of reactive arthritis in children and adolescents with proposed treatment algorithm.
Keywords: Arthritis